2011
DOI: 10.5513/jcea01/12.2.924
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Nitrogen in the Soils of Eastern Poland as Influenced by Type of Crop, Nitrogen Fertilisation and Various Organic Fertilisers

Abstract: This paper describes the influence of nitrogen and organic fertilisation and the type of crops on the contents of NO 3 -N in arable land. The large-scale environmental research was carried out in [2004][2005][2006]. Soil samples were taken from 411 places throughout the Lublin region in two seasons: spring and autumn.The concentration of nitrate(V) depended on fertilisation and crops. It was found that application of N-fertiliser above 121 kg N ha -1 caused a significant increase in the nitrate(V) concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
1
5
0
3
Order By: Relevance
“…It concurs with published literature as a potential issue throughout Europe, including the northern and central case study MSs: the UK [46], Sweden [47], Poland [48], France [49], northern Spain [50,51] and Germany [52]. Italy [53,54] and Greece [55] in the south also report NO 3 ¡ leaching from cultivated land, a factor further influenced by irrigation during drier periods of the year [56].…”
Section: ¡1supporting
confidence: 67%
“…It concurs with published literature as a potential issue throughout Europe, including the northern and central case study MSs: the UK [46], Sweden [47], Poland [48], France [49], northern Spain [50,51] and Germany [52]. Italy [53,54] and Greece [55] in the south also report NO 3 ¡ leaching from cultivated land, a factor further influenced by irrigation during drier periods of the year [56].…”
Section: ¡1supporting
confidence: 67%
“…Determination of N contents in agricultural soils in spring is a useful tool to assess requirements for nitrogen fertilisation, whilst the distribution of NO 3 –N in soil in autumn evaluates possible nitrogen losses by leaching during winter [16]. It was also assumed that soil agricultural practices influence the activity of microorganisms which participate in various nitrogen transformation processes in soil [45].…”
Section: Discussionmentioning
confidence: 99%
“…The average content of mineral nitrogen in the Polish soils is in the range of 76–90 kg N/ha in spring and 89–97 kg N/ha in autumn [14, 15]. Dresler et al [16] found that application of N -fertiliser above 121 kg N/ha resulted in a significant increase in the NO 3 –N content in the surface soil layer. According to the Polish Statistical Office report [17], the use of mineral fertilisers in Lubelskie voivodeship amounted to 141.7 kg/ha, with nitrogen, phosphorus and potassium fertilisers accounting for 50, 20 and 38 %, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…According to Anggria et al [26], the share of N-NH 4 and N-NO 3 in N min depends on the type of organic matter, its application to soil, and microbiological activity, as well as the water and air content of soil. When analyzing agricultural soils in eastern Poland in 2004-06, Dresler et al [27] stated that N-NO 3 content in soils depends on the dosage of nitrogen and type of fertilizer (organic, mineral), the species of cultivated crop, atmospheric conditions, and the physico-chemical properties of the soil. The determined forms of nitrogen were used to calculate Pearson's simple correlation coefficients (Table 4).…”
Section: Effects Of Long-term Organic 2075mentioning
confidence: 99%